2011
DOI: 10.1007/s00266-011-9806-9
|View full text |Cite
|
Sign up to set email alerts
|

Lazy S-curve Epicanthoplasty in Asian Blepharoplasty

Abstract: Lazy S-curve epicanthoplasty is a reliable and effective method to eliminate not only the epicanthal fold but also the undesirable orbicularis oculi muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Mustarde's 4‐flap method 13 works well in cases of severe epicanthal folds with rare recurrences; however, in Asians, the scar is noticeable, and therefore, the medial canthal area appears unnatural. Lazy S‐curve epicanthoplasty needs to be continuous with the double‐eyelid incision 6 . Invisible scar medial epicanthoplasty hides the incision in an area where it cannot be seen directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mustarde's 4‐flap method 13 works well in cases of severe epicanthal folds with rare recurrences; however, in Asians, the scar is noticeable, and therefore, the medial canthal area appears unnatural. Lazy S‐curve epicanthoplasty needs to be continuous with the double‐eyelid incision 6 . Invisible scar medial epicanthoplasty hides the incision in an area where it cannot be seen directly.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of surgical techniques to remove the epicanthus have been reported in the literature, including various Z plastics, 1,2 the Y‐V advancement flap, 3 V‐W plasty, 4 Mustarde's four‐flap technique, 5 lazy S‐plasty, 6 and the skin redraping method 7 . However, most techniques include a complex design, which may lead to increased scarring of the epicanthal area.…”
Section: Introductionmentioning
confidence: 99%
“…Hirohiko et al and Yulan et al verified that the preseptal orbicularis muscle was the anatomical etiologic factor of the epicanthus in their anatomical examination. 11,12 Hirohiko et al found that the preseptal orbicularis fasciculi ran obliquely around the epicanthus and coincided with the direction of the epicanthus in their anatomical study. They also reasoned that the epicanthus formation depended on the intermuscular fibers of the oblique direction of the preseptal orbicularis muscle.…”
Section: Evolution Of the Epicanthus (Kwon's Theory): Etiology And Prmentioning
confidence: 91%
“…Various modifications of the Z-plasty technique have been described and all claim excellent results. Examples include the modified Z-plasty [9,11,15,16,22], lazy S technique [19], discrepant Z-plasty [17], and multiple Z-plasty [18]. It is important to note that subcutaneous tissue dissection and orbicularis oculi myectomy is performed in all later publications.…”
Section: Z-plasty and Its Modificationsmentioning
confidence: 97%